2019
DOI: 10.1177/0954008319830468
|View full text |Cite
|
Sign up to set email alerts
|

Influence of HTPB prepolymer on achieved properties of composite solid propellant

Abstract: Changes/variations during manufacturing and storage of free radical-polymerized hydroxyl-terminated polybutadiene resin/prepolymer (widely used binder for the composite solid propellants) are not reflected in terms of appreciable change in the hydroxyl value. As a result, cured properties of the propellant mixed using the given formulation finalized by keeping R ratio (NCO/OH ratio) within 0.7–0.9 did not yield predicted mechanical properties. Investigations carried out subsequently, by the authors, identified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…As evident from Table 8, the peel strength of EPDM without Kevlar evaluated for each interface exceeded the respective minimum required value and the values are well comparable to those of Nitrile rubber based insulation also. Significant finding is that bonding agent for Nitrile rubber based insulation to HTPB based propellant works well with EPDM to HTPB based propellant too 39 . As EPDM without Kevlar itself offered the required interfacial bonding strength, there is adequate confidence that interfacial bonding strength of EPDM with Kevlar would be some order higher.…”
Section: Resultsmentioning
confidence: 99%
“…As evident from Table 8, the peel strength of EPDM without Kevlar evaluated for each interface exceeded the respective minimum required value and the values are well comparable to those of Nitrile rubber based insulation also. Significant finding is that bonding agent for Nitrile rubber based insulation to HTPB based propellant works well with EPDM to HTPB based propellant too 39 . As EPDM without Kevlar itself offered the required interfacial bonding strength, there is adequate confidence that interfacial bonding strength of EPDM with Kevlar would be some order higher.…”
Section: Resultsmentioning
confidence: 99%
“…Type‐5 exhibits peel strength values, which are higher than those achieved for each of the above interfaces in respect of Type‐1. It is surprising to note that, the bonding agent originally developed for the bonding of proven nitrile rubber based insulation with HTPB based composite solid propellant, proves to be equally effective for the bonding of EPDM‐P insulation of given types with the HTPB based composite solid propellant 25 . Thus it is confirmed beyond doubt that peroxide cured EPDM insulation possesses required interfacial bonding strength as warranted by insulation of large CRMC, despite the absence of hypalon (polar polymer) and Kevlar filler.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, batch‐to‐batch variation in HTPB prepolymer in terms of molecular weight and molecular weight distribution may be the root cause for the variation or uncertainty in the cured mechanical properties of the propellant. Further, the authors concluded that the viscosity of the HTPB prepolymer, if determined accurately, is indicative of changes in the molecular mass [56]. Regarding this, as mentioned, the viscosity of the HTPB increases with an increase in vinyl content [38].…”
Section: Introductionmentioning
confidence: 99%